Placental blood flow sensing and regulation in fetal growth restriction. (15th September 2021) - Morley, L.C.; Debant, M.; Walker, J.J.; Beech, D.J.; Simpson, N.A.B.
Abstract: The mechanical force of blood flow is a fundamental determinant of vascular homeostasis. This frictional stimulation of cells, fluid shear stress (FSS), is increasingly recognised as being essential to placental development and function. Here, we focus on the role of FSS in regulating fetoplacental circulatory flow, both in normal pregnancy and that affected by fetal growth restriction (FGR). The fetus is reliant on placental perfusion to meet its circulatory and metabolic demands. Failure of normal vascular adaptation and the mechanisms enabling responsive interaction between fetoplacental and maternal circulations can result in FGR. FSS generates vasodilatation at least partly through the release of endothelial nitric oxide, a process thought to be vital for adequate blood flow. Where FGR is caused by placental dysfunction, placental vascular anatomy is altered, alongside endothelial dysfunction and hypoxia, each impacting upon the complex balance of FSS forces. Identifying specific mechanical sensors and the mechanisms governing how FSS force is converted into biochemical signals is a fast-paced area of research. Here, we raise awareness of Piezo1 proteins, recently discovered to be FSS-sensitive in fetoplacental endothelium, and with emerging roles in NO generation, vascular tone and angiogenesis. We discuss the emerging concept that activating mechanosensors such as Piezo1 ultimately results in the orchestrated processes of placental vascular adaptation. Piecing together the mechanisms governing endothelial responses to FSS in placental insufficiency is an important step towards developing new treatments for FGR. Graphical abstract: Image 1